Double characteristic BNO-SPI-TENGs for robust contact electrification by vertical contact separation mode through ion and electron charge transfer. (February 2018) - Cheedarala, Ravi Kumar; Duy, Le Chau; Ahn, Kyoung Kwan
Abstract: Contact-electrification is a conventional triboelectrification technique for generating current through charge transfer when two different polarized materials are brought into contact. For the first time, in-built alternate hydrophilic and hydrophobic nano channels were developed where both ionic and electronic charge transfer mechanisms were realized through contact separation mode between BNO-SPI films and PTFE. In this paper, we examined the dynamic interaction between these materials and observed adequate output performance. The novel BNO-SPI-TENGs (i.e. SO3H.BNO-SPI-TENG, SO3Li.BNO-SPI-TENG, and SO3H.TEA.BNO-SPI-TENG) produced 75 V and 1 µA, 43 V and 0.6 µA, and 9 V and 0.13 µA of open-circuit voltages (Voc) and short-circuit currents (Jsc) at 6 Hz, respectively. Particularly, the SO3H-BNO-SPI was dramatically boosted up the performance of TENG, up to 733% of Voc and 669% of Jsc, with respect to the SO3H.TEA-BNO-SPI because the mobility of H+ ions is very high on the device surface compared to the other two Li+ and TEA bulky ions. The developed dual characteristic BNO-SPI-TENGs are very good candidates for fulfilling the need for alternate contact separation mode TENGs. Graphical abstract: Highlights: Novel double characteristic hydrophilic and hydrophobic nano channel oriented BNO-SPI films were proposed. Contact electrification process was took place on the BNO-SPI films that followed ion and electron transfer mechanisms. An electron-donor-acceptor complex mechanism was proposed for the electron transfer mechanism. High triboelectric (Voc ) and (Jsc ) were observed from BNO-SPI-TENGs, in particular, 75 V and 1 µA for SO3 H.BNO-SPI-TENG at 6 Hz.